(untitled) (Research, Society and Development, 2022)
This article describes the importance of physical therapy in the treatment of knee joint degeneration, known as gonarthrosis. This joint is critical to the lower extremity because it provides stability and flexibility for all aspects of kinematics. As the knee joint is a weight-bearing joint, it is prone to degenerative changes such as arthropathy. Within the methodology, articles published between the years 2002 to 2019 were used, which were analyzed through an analytical form. The following topic presents a brief explanation about what is gornathrosis, this work will also point out indications of physiotherapy in the treatment of gornathrosis. Physiotherapy is very important for the improvement of this patient, aiming to reduce pain, reduce demands on the knee joint, increase joint mobility, promote more cartilage nutrition and reduce muscle stiffness and weakness. Finally, the benefits of physiotherapy are evidenced, taking into account the positive evolution of patients.